Consumer behaviour toward a new league and teams: television audiences as a measure of market acceptance. Issue 2 (4th March 2022) - Fujak, Hunter; Frawley, Stephen; Lock, Daniel; Adair, Daryl
ABSTRACT: Research question: Research into new sport teams has maintained a narrow focus on season ticket holders. This is redressed in this study by determining whether immediate preferences towards new local teams can be observed in the broader viewing behaviour of the general population within local markets. The consumption of new sport teams is then tracked longitudinally to understand the influence of consumer novelty on market behaviour. Research methods: The study analysed television ratings data of a new Australian cricket league. The period of analysis spanned five seasons from 2013/2014 through to 2017/2018. Data analysis included independent samples t -tests and hierarchical linear modelling. Results and findings: Each local market exhibited an immediate preference for their local team. Local viewing preference for local teams did not grow over time, with the relative audience of local and non-local team fixtures increasing proportionally over the period. The league appears to be towards the end of its novelty phase, evidenced by a stabilisation in viewing commitment yet retraction in base audience size between season three and five. Implications: The ability of new teams to solicit immediate local viewing preferences within the general population confirms the salience of geography as a foundational component of team identity. New teams should strategically consider their alignment to a suburban, city, state, or regional identity. That preference towards local teams did not increase within local markets reflects a critical theoretic distinction from more identified fan segments in which connection to team is thought to typically grow over time.